2017
DOI: 10.1371/journal.pone.0183902
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes exhibit fibrillar pharmacology in primates

Abstract: Nanomedicine rests at the nexus of medicine, bioengineering, and biology with great potential for improving health through innovation and development of new drugs and devices. Carbon nanotubes are an example of a fibrillar nanomaterial poised to translate into medical practice. The leading candidate material in this class is ammonium-functionalized carbon nanotubes (fCNT) that exhibits unexpected pharmacological behavior in vivo with important biotechnology applications. Here, we provide a multi-organ evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Alternatively, the nanosensors may be embedded directly in a hydrogel matrix, as has been investigated with carbon nanotubes in vivo, finding no local inflammation ( 27 ). Further, although we expect no exposure of the nanosensor complex when immobilized in the implant device, well-dispersed, purified SWCNTs such as those used here do not exhibit any immunogenic or toxic effects ( 36 , 53 ).…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, the nanosensors may be embedded directly in a hydrogel matrix, as has been investigated with carbon nanotubes in vivo, finding no local inflammation ( 27 ). Further, although we expect no exposure of the nanosensor complex when immobilized in the implant device, well-dispersed, purified SWCNTs such as those used here do not exhibit any immunogenic or toxic effects ( 36 , 53 ).…”
Section: Discussionmentioning
confidence: 91%
“…Fibrillar macromolecules that are rigid and have high-aspect ratios exhibit unique pharmacological properties in vivo compared to high molecular weight globular molecules 11 , 12 . Our lab has been investigating functionalized carbon nanotubes (fCNT) as synthetic molecular platforms for gene and drug delivery 13 20 . Several physicochemical properties are common to CNT and CNC including high surface area, rigid fibrillar shape, high aspect ratio and a minimal aqueous solubility of the unfunctionalized starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of CNT with multiple copies of primary amines provided a means to greatly improve water-solubility and biocompatibility as well as an expedient means to engineer a drug excipient for loading and transport of pharmacologically active cargo. The exceptional pharmacokinetic behavior of functionalized CNT in rodents and nonhuman primates is best described by rapid blood clearance, cell specific-accumulation in kidney and liver and intact renal elimination in the urine 13 15 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found no safety issues with MNPs, which comports with our prior work in healthy mice 17 . However, the nanotube-based drug carrier also demonstrated safety in non-human primates 37,38 . We expect similar pre-clinical pharmacokinetic studies to further the possibility of MNP clinical translation.…”
Section: Discussionmentioning
confidence: 99%